Characterising englacial R-channels using artificial moulins. Issue 271 (14th October 2022) - Pohle, Annegret; Werder, Mauro A.; Gräff, Dominik; Farinotti, Daniel
Abstract: The englacial and subglacial drainage systems exert key controls on glacier dynamics. However, due to their inaccessibility, they are still only poorly understood and more detailed observations are important, particularly to validate and tune physical models describing their dynamics. By creating artificial glacier moulins – boreholes connected to the subglacial drainage system and supplied with water from surface streams – we present a novel method to monitor the evolution of an englacial hydrological system with high temporal resolution. Here, we use artificial moulins as representations for vertical, pressurised, englacial R-channels. From tracer and pressure measurements, we derive time series of the hydraulic gradient, discharge, flow speed and channel cross-sectional area. Using these, we compute the Darcy–Weisbach friction factor, obtaining values which increase from 0.1 to 13 within five days of channel evolution. Furthermore, we simulate the growth of the cross-sectional area using different temperature gradients. The comparison to our measurements largely supports the common assumption that the temperature follows the pressure melting point. The deviations from this behaviour are analysed using various heat transfer parameterisations to assess their applicability. Finally, we discuss how artificial moulins could be combined with glacier-wide tracer experiments to constrain parameters of subglacial drainage more precisely.